Financial markets and institutions - Mishkin, Frederic S. (Pearson Prentice Hall, 2009)
In Financial Markets and Institutions, best-selling authors Mishkin and Eakins provide a practical introduction to prepare readers for today’s changing landscape of financial markets and institutions. A unifying framework uses a few core principles to organize readers' thinking then examines the models as real-world scenarios from a practitioner’s perspective. By analyzing these applications, readers develop the critical-thinking and problem-solving skills necessary to respond to challenging situations in their future careers.